Pneumatology in the digital age: Reimagining the Holy Spirit’s role in Trinitarian theology - Nthakheni, Rendani C.; Mudau, Ndidzulafhi (African Journal of Pentecostal Studies, 2025)
BackgroundThe Holy Spirit is becoming increasingly marginalised in contemporary Christian theology and practice, particularly as churches grapple with the technological and philosophical implications of the Fourth Industrial Revolution (4IR).ObjectivesThis study examines pneumatological theory within Trinitarian theology through the lens of 4IR technologies, addressing systematic marginalisation, reductionism and insufficient theological inquiry of the Holy Spirit.MethodThe study employs qualitative theological approaches that include historical-critical analysis and systematic theology, as well as a thorough biblical assessment of major pneumatological texts and an investigation into the historical evolution of Trinitarian theology.ResultsThe study finds important gaps in present pneumatological understanding, establishes the Holy Spirit’s distinct personhood within the Trinity and indicates the Spirit’s critical role in both church and individual spirituality that goes beyond functional dimensions.ConclusionA strong pneumatological framework is required for Christians navigating the digital age, one that recognises the Spirit’s role in technical innovation while maintaining theological purity.ContributionThis study advances theological scholarship by proposing novel models for understanding the Holy Spirit’s operation in digital environments and providing practical applications of pneumatological insights for current Christian communities using 4IR technology.